Rancang Bangun Deteksi Tingkat Kerusakan Current Tranformer Secara Online di Gardu 20 kV PT PLN UP3 Malang - fauzy afriansyah; Bambang Dwi Sulo; Bambang Minto Basuki (SCIENCE ELECTRO, 2022)
AbstractMeasurement errors are often found on CT which result in energy measurements not being collected perfectly, therefore a tool design is made to detect damage to CT. The working principle of this tool is knowing the error in the CT through the current sensor installed in the neutral current wiring from the kWH meter to the CT, if the neutral current exceeds 1 ampere, it can be used as a reference to re-check the accuracy of the CT because there are indications that the measurement is out of class. From the results of testing the accuracy of the sensor on this tool, a difference of 0.02 amperes is obtained, this value is included in the normal category for a measurement sensor so that this tool can be implemented at PT PLN substations. By implementing this tool, it detects the initial level of CT damage, making it easier to make technical improvements so that the customer's energy consumption measurement can be billed perfectly.Keywords- Current Transformer (CT), Measurement Accuracy, Neutral Current AbstrakSering ditemukan error pengukuran pada CT yang mengakibatkan pengukuran energi tidak tertagih dengan sempurna, maka dari itu dibuatlah rancang bangun alat untuk mendeteksi kerusakan pada CT. Prinsip kerja alat ini mengetahui error pada CT melalui sensor arus yang dipasang di wiring arus netral balikan dari kWH meter ke CT, jika didapat arus netral melebihi 1 ampere maka bisa menjadi acuan untuk memeriksa ulang akurasi CT karena ada indikasi pengukurannya keluar kelas. Dari hasil pengujian akurasi sensor pada alat ini didapat selisih 0,02 ampere, nilai tersebut masuk kategori normal untuk sebuah sensor pengukuran sehingga alat ini sangat bisa di implementasikan di gardu PT PLN. Dengan mengimplementasikan alat tersebut mendeteksi awal tingkat kerusakan CT sehingga mempermudah melakukan perbaikan teknik agar pengukuran energi pemakaian pelanggan bisa tertagih dengan sempurna.Kata Kunci- Trafo Arus (CT), Akurasi Pengukuran, Arus Netral